Common carotid wall elasticity and intima-media thickness examinations by means of ultrasound - POWAŁOWSKI, T.; TRAWIŃSKI, Z.; HILGERTNER, L. (Archives of Acoustics, 2000)
The aim of this study was to examine the relation between the intima-media thickness and the wall elasticity measured simultaneously in the same cross-section of the common carotid artery. A group of 40 persons (19 healthy and 21 with hypertension and/or atherosclerosis) aged 22 to 81 were diagnosed by means of ultrasound. A high correlation occurred between the wall stiffness coefficient α; and the intima-media thickness (r = 0.950, p < 0. 00001).